Global Collective Intelligence in Technological Societies: as a result of Collaborative Knowledge in combination with Artificial Intelligence - Piedra Calderón, Juan Carlos; Rainer, J. Javier (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
The big influence of Information and Communication Technologies (ICT), especially in area of construction of Technological Societies has generated big social changes. That is visible in the way of relating to people in different environments. These changes have the possibility to expand the frontiers of knowledge through sharing and cooperation. That has meaning the inherently creation of a new form of Collaborative Knowledge. The potential of this Collaborative Knowledge has been given through ICT in combination with Artificial Intelligence processes, from where is obtained a Collective Knowledge. When this kind of knowledge is shared, it gives the place to the Global Collective Intelligence.
Keywords: artificial intelligence; collaboration; ICT; intelligent systems; knowledge management; IJIMAI